ANALYTICS FOR THE INTERNET OF THINGS IOT - ANDREW MINTEER (BIRMINGHAM UK PACKT PUBLICATIONS, 2017)
INTELLIGENT ANALYTICS FOR YOUR INTELLIGENT DEVICES
ANALYTICS FOR THE INTERNET OF THINGS
COMPUTERS
Keywords: INTERNET OF THINGS; COMPUTERS